Strategi Pembelajaran Konjugasi Kata Kerja Bahasa Jepang pada Pembelajar Otodidak: Learning Strategies for Japanese Verb Conjugation in Self-Taught Learners - Rani Arfianty; Gumarpi Rahis Pasaribu; Syahban Danas; Billy Joel (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study focuses on Japanese verb conjugation learning among beginner-level self-directed learners and to examine the relationship between learning strategies and conjugation accuracy. The research employed a descriptive quantitative approach combined with qualitative analysis involving three self-directed learners at approximately JLPT N5 level. Data were collected through a Likert-scale questionnaire on learning strategies and a conjugation test covering polite form (ます形), te-form (て形), past form (た形), negative form (ない形), and phonological changes in godan verbs. The findings indicate a positive tendency between structured learning strategies and higher conjugation accuracy. Learners who actively classified verbs, engaged in repeated practice, and performed self-correction achieved significantly higher test scores compared to those who relied primarily on exposure without systematic strategies. The most noticeable differences appeared in godan verb conjugation, which requires pattern recognition and phonological rule generalization. These results suggest that the quality of learning strategies plays a more crucial role than the amount of study time in developing a stable morphological system among self-directed Japanese language learners.